An integrated TOPSIS model with exponential intuitionistic entropy measure for multi-attribute decision-making (MADM) - Omar, Ayasrah; Faiz, Mohd Turan; Sheikh Muhammad Hafiz Fahami, Zaina (Springer Singapore, 2024)
The determination of attribute weights in solving multi-attribute decision-making (MADM) problems is crucial and significantly impacts the results. Many researchers have highlighted the effectiveness of deriving attribute weights objectively based on the assessments provided by decision-makers for MADM problems. One approach involves using entropy measures to determine weights based on the given ratings. This paper introduces a novel intuitionistic fuzzy entropy measure that takes the form of an exponential function. This new entropy measure is combined with the TOPSIS method to propose a new decision-making method for solving MADM problems. The proposed method does not require attribute weights, thereby eliminating the need for their determination.